2004
DOI: 10.1097/00008506-200401000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Jugular Bulb Oxygen Saturation Under Propofol or Sevoflurane/Nitrous Oxide Anesthesia During Deliberate Mild Hypothermia in Neurosurgical Patients

Abstract: Sevoflurane and propofol have been widely used as anesthetic agents for neurosurgery. Recent evidence has suggested that the influence of these anesthetics on cerebral oxygenation may differ. In the present study, the authors investigated jugular bulb oxygen saturation (SjO2) during propofol and sevoflurane/nitrous oxide anesthesia under mildly hypothermic conditions. After institutional approval and informed consent, 20 patients undergoing elective craniotomy were studied. Patients were randomly divided to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…In the current study, the postinduction baseline SjvO 2 was higher in S/N than in P/R group, being in agreement with previous observations. [15][16][17][18] In addition, the magnitude of decreases in SjvO 2 in BCP was less pronounced (11 Ϯ 10% vs. 23 Ϯ 9%, P ϭ 0.0006) and a reduced SjvO 2 value (less than 50%) was less frequently observed in S/N than in P/R group. Furthermore, the incidence of SjvO 2 less than 40% was null in S/N group as compared with 29% in P/R group (P ϭ 0.0109).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In the current study, the postinduction baseline SjvO 2 was higher in S/N than in P/R group, being in agreement with previous observations. [15][16][17][18] In addition, the magnitude of decreases in SjvO 2 in BCP was less pronounced (11 Ϯ 10% vs. 23 Ϯ 9%, P ϭ 0.0006) and a reduced SjvO 2 value (less than 50%) was less frequently observed in S/N than in P/R group. Furthermore, the incidence of SjvO 2 less than 40% was null in S/N group as compared with 29% in P/R group (P ϭ 0.0109).…”
Section: Discussionmentioning
confidence: 84%
“…[12][13][14] Indeed, cerebral oxygen balance is better maintained by sevoflurane-based than by propofol-based anesthesia when patients are positioned supine. [15][16][17][18] In this context, it is also possible that the margin of safety against an impaired cerebral oxygenation would be greater with sevofluranebased than with propofol-based anesthesia in BCP. The choice of anesthetic technique may also influence hemodynamic stability in the sitting position.…”
mentioning
confidence: 99%
“…Secondary insults can occur during any phase of TBI from pre-hospital to the intensive care but the intraoperative period is physiologically distinct. While TBI itself can lead to myocardial and pulmonary dysfunction, 20,21 the anesthetic agents also affect cerebral 2224 and cardiovascular physiology. 25,26 In addition, surgical intervention leads to fluid shifts and blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in brain tumor patients have reported a decrease in jugular venous oxygen saturation (SjvO 2 ) after hyperventilation and during additional hypothermia with up to 50% of patients having SjvO 2 Ͻ50%. 16,33,34 Although a previous study demonstrated SjvO 2 values of 40%-45% were associated with metabolic failure and secondary brain damage in headinjured patients, 35 we are uncertain how the ischemic threshold should be applied during anesthesia. It is possible that inadvertent cerebral ischemia may outweigh the benefits of hyperventilation, and should be the subject of further investigation.…”
Section: Discussionmentioning
confidence: 99%